MALE AND FEMALE SOCIAL MEDIA INFLUENCERS: THE IMPACT OF GENDER ON EMERGING ADULTS - Komathi Lokithasan; Salomi Simon; Nur Zahrawaani Binti Jasmin; Nur Ajeerah Binti Othman (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Social media influencers are people who have established a reputation for themselves on social media. Nowadays, a social media influencer has played the important role of a marketing tool for organizations. Organizations use the power of social media influencers to influence and persuade consumers through social media. It is because social media influencers have a huge number of followers in their social media, thus, social media influencer could promote to and reach a large number of consumers in a short time. The result is more effective than celebrity endorsement for small-and-medium-sized enterprises (SME). This research is to study the perceptions of emerging adults on the difference between male and female social media influencers’ style of promotion. Qualitative method is used by conducting a focus group and content analysis to compare the impact of male and female social media influencers towards emerging adults. Findings showed that female respondents are influenced by influencers who promote beauty products while male respondents are drawn to technology and gaming products. The most important factors mentioned by the respondents in the impact of the social media influencers’ posts are the entertainment factor and followed by informativeness.